Defending behavior of peer victimization in school and cyber context during childhood and adolescence: A meta-analytic review of individual and peer-relational characteristics - Ma, Ting-Lan; Meter, Diana J; Chen, Wei-Ting; Lee, Yen (Psychological bulletin, 2019)
Adolescent defending of peer victimization in the school and cyber context has received increased attention in developmental science and is an important component of antibullying interventions. However, the overall prevalence, and individual characteristics that correlate with defending in adolescence, have not been systematically and statistically reviewed. Framed in Bronfenbrenner's social-ecological theory, this meta-analytic review included 172 reports out of 155 studies of defending including 150,978 children and adolescent participants from 4 continents (i.e., North America, Europe, Asia, and Australia) to analyze two aspects: (1) the average proportion of defenders in the population and (2) associations between defending and individual and peer-relational correlates of defending in school and cyber contexts. Using mixed-effects modeling, our results confirmed prior findings of gender differences (favoring girls) and age differences (favoring younger children) in defending. We found positive correlations between defending and affective empathy, cognitive empathy, experiences of peer victimization, self-efficacy, popularity, and acceptance, and a negative correlation between defending and moral disengagement. We also found substantial heterogeneity in these effect sizes. The reporter of defending consistently moderated all mean effect sizes. Implications for prevention efforts and future research are discussed. (PsycINFO Database Record (c) 2019 APA, all rights reserved).